Engineering economic principles - Steiner, Henry Malcolm (New York ; London : McGraw Hill Education, 1996)
Designed for the core course in engineering economics, this text provides an introduction to the field. It focuses on central concepts, with practical examples complementing the explanations. A disk (for use with Lotus, Excel or Quatro) contains solutions to selected examples from the text.
Investment choice -- equivalence -- interest and financial mathematics -- present worth -- annual worth -- the benefit/cost ratio -- the internal rate of return -- multiple alternatives -- the effect of income tax on economic analysis -- inflation -- risk -- loans -- capital budgeting -- the cost of capital -- retirement and replacement -- sector analysis and viewpoint -- sensitivity analysis.
Includes bibliographical references and index.
Keywords: ENGINEERING ECONOMY